MERANTAU SEBAGAI WADAH PEMBENTUKAN KARAKTER DALAM NOVEL-NOVEL INDONESIA BERLATAR MINANGKABAU - Armini Arbain (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2022)
This article aims to describe the tradition of merantau in Indonesian novels depicting the Minangkabau community. The tradition of merantau is a tradition that has its roots in Minangkabau and intends to shape the character of the younger generation. To analyze the merantau activity in the novel, the sociology of literature approach was used, especially genetic structuralism. The theory of genetic structuralism is relevant for dismantling the merantau activity in novels because this theory related closely to the genetic aspects of a novel. This study concludes that merantau in the Minangkabau community can shape the character of creating youth. The characters formed are tenacious, have a sense of sympathy and cooperation, and have a strong spirit and practice religious teachings.